EFFECT OF WATER AND WATER-ETHANOL EXTRACTS OF ELEUTHERINE AMERICANA (AUBL.) MERR. BULB ON IN-VITRO PLATELET ANTIAGREGATION ACTIVITY AND DETERMINATION OF NITROGEN OXIDE VASODILATOR LEVEL ON MALE WISTAR RATS - EL MUTTAQIEN, SJAIKHURRIZAL
Eleutherine americana (Aubl.) Merr or known as bawang kapal has been investigated as cardioprotector, though the specific mechanism has not been known. The research of platelet aggregating activities was performed by in vitro test on human blood plasma. The activity of platelet antiagregation was measured by Bohr method. Samples were given in a set of Eleutherine americana (Aubl.) Merr water and water-ethanol extract different concentrations and were compared to asetosal in order to get IC50 relative. Griees principle reaction, was used for determination of nitrite concentration in blood. Water extract of Eleutherine americana (Aubl.) Merr. was given in 225 mg/Kg dosage while water-ethanol extract was given in 112.5 mg/Kg dosage. The standard, which is used in this research, was ISDN (Isosorbide Di-Nitrate). The water-ethanol extract had higher effect as a platelet antiagregation agent compared to the water extract solution (IC50 ethanol extract = 93,34 ug/mL, IC50 water extract = 230,39 ug/mL, IC50 Asetosal = 258,15 ug/mL). The water-ethanol extract had activity on increasing nitrite concentration in blood, with the average of maximum nitrite concentration was 15.06 + 2.97 uM, ISDN standard was 22.45 + 6.3 uM, while the water extract did not show an equally-increasing effect. Eleutherine americana (Aubl.) Merr water-etanol extract had an activity as platelet antiagregating agent and NO enhancer concentration in blood, while the water extract only had an activity as platelet antiagregating agent.